Le beau sexe. Quelques pistes de réflexion sur les chirurgies sexuelles cosmétiques - Hélène Martin (Genre, Sexualité et Société)
Cosmetic sexual surgeries are medical practices which produce sexed bodies to improve gendered and sexual functioning. They are also seen, in this article, as practices putting into question the naturalistic argument of sex determination. Though ocurring in a context that endorses genital morphologic diversity, they promote less conformity with morphological models than improvement of psychological and relational well-being. But, as the analysis of the arguments legitimizing the interventions shows, cosmetic sexual surgeries reproduce gender relations and make the social standard an issue of individual responsibility : to feel good in a (sexualized) body and in (sexual) relations. Thus challenges to the naturalistic argument are not antinomic with the reproduction of gender relations.